2013
DOI: 10.1590/s0034-737x2013000400004
|View full text |Cite
|
Sign up to set email alerts
|

Análise econômica da terminação de bovinos de corte em confinamentos no estado de Minas Gerais: estudo de caso

Abstract: Economic analysis of the finishing of beef cattle in feedlots in the state of Minas Gerais: a case studyThe objective of this study was to evaluate the profitability of the beef cattle finishing in feedlot. Particularly, it was also intended to identify the components of the total and effective operational cost of greater impact on the production of meat and estimate the breakeven point. Data collection was carried out from January to December of 2009 in two beef cattle production systems, located in Sete Lago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 11 publications
2
3
0
3
Order By: Relevance
“…The behavior of the estimated costs in this study are consistent with other studies involving the termination of beef cattle feedlot (MISSIO et al, 2009;LOPES et al, 2013;PACHECO et al, 2014). These results demonstrate the importance of planning the marketing season of animals, and the purchase of raw materials for making the diet as strategies that can result in reduction in the total cost and maximization of total revenues, providing this way, the economic success of the activity.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The behavior of the estimated costs in this study are consistent with other studies involving the termination of beef cattle feedlot (MISSIO et al, 2009;LOPES et al, 2013;PACHECO et al, 2014). These results demonstrate the importance of planning the marketing season of animals, and the purchase of raw materials for making the diet as strategies that can result in reduction in the total cost and maximization of total revenues, providing this way, the economic success of the activity.…”
Section: Resultssupporting
confidence: 89%
“…The higher slaughter weight, the greater the bonus, leading to reflect on the possibility of extending the time to feed and / or enhance the nutritional level of the diet in order to reach this goal. However, it is known the consequent increase in operating expenses, which many authors (MISSIO et al, 2009;LOPES et al, 2013) reported that disregarding the cost of acquisition of feeder cattle, the feed costs represent more than 70% of the variable costs and can put the system in a delicate situation when analyzing the cost-benefit.…”
Section: Introductionmentioning
confidence: 99%
“…A rentabilidade desse sistema foi superior comparativamente a outros trabalhos apresentados na literatura. Lopes et al (2013) apresentaram rentabilidade máxima de 10,36% analisando dois sistemas de confi namento. Lopes e Magalhães (2005) também realizaram um estudo de caso com a terminação de bovinos de corte em condições de confi namento e obtiveram uma rentabilidade de apenas 1,3%.…”
Section: Discriminaçãounclassified
“…Many researchers (Demeu et al, 2012;Demeu et al, 2013;Lopes et al, 2013;Mandarino et al, 2013;Geron et al, 2014;Raupp and Fuganti, 2014) have shown the influence of the purchase price of animals on the economic return of the finishing process. This item accounts for 70% of the total costs of the operation, i.e., knowing this exchange rate (sale price of the arroba of fat cattle/purchase price of the arroba of the cattle to be feedlot-finished) is fundamental in the predictability and decision-making for the finishing operation (Machado and Berger, 2012).…”
Section: Discussionmentioning
confidence: 99%